Cefepime and Amoxicillin Increase Metabolism and Enhance Caspofungin Tolerance of Candida albicans Biofilms - Cordeiro, Rossana de Aguiar; Evangelista, Antonio Jose de Jesus; Serpa, Rosana; Andrade, Ana Raquel Colares de; Mendes, Patrícia Bruna Leite; Oliveira, Jonathas Sales de; Alencar, Lucas Pereira de; Pereira, Vandbergue Santos; Lima-Neto, Reginaldo Gonçalves; Brilhante, Raimunda Nogueira; Sidrim, José Júlio Costa; Maia, Débora Castelo Brancode Souza Collares; et al. (Frontiers in Microbiology, 2019)
It is well known that prolonged antibiotic therapy alters the mucosal microbiota composition, increasing the risk of invasive fungal infection in immunocompromised patients. The present study investigated the direct effect of β-lactams antibiotics, cefepime (CEF) and amoxicillin (AMOX) on biofilm production by Candida albicans ATCC 10231. Antibacterials at the peak plasmatic concentration of each drug were tested against biofilms grown on polystyrene surfaces. Biofilms were evaluated for biomass production, metabolic activity, carbohydrate and protein contents, proteolytic activity, ultrastructure and tolerance to antifungals. CEF and AMOX enhanced biofilm production by C. albicans ATCC 10231, stimulating biomass production, metabolic activity, viable cell counts, proteolytic activity, as well as increased biovolume and thickness of these structures. In addition, it was shown that AMOX increased the amount of chitin in these biofilms, making them more tolerant to caspofungin. Finally, it was seen that, in response to AMOX, C. albicans biofilms produce Hsp70 – a protein with chaperone function related to stressful conditions. These results may have a direct impact on the pathophysiology of opportunistic invasive fungal infections in patients at risk.